Implementasi Manajemen Strategis Pada Lembaga Wilayatul Hisbah Dalam Penegakan Syariat Islam di Kota Aceh - Chysara, Daris Iqbal; Yuliani, Yuliani; Rustandi, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2022)
Aceh is an area that is given the authority to regulate and implement the law in accordance with Islamic law in the life of its own government. Â This study aims to find out and understand how the formulation of the Wilayatul Hisbah strategy in Banda Aceh City in the Enforcement of Islamic Law, Knowing the implementation of the Wilayatul Hisbah strategy in Banda Aceh City, and knowing the evaluation of strategies carried out by the Wilayatul Hisbah Institution of Banda Aceh City which is oriented towards the enforcement of Islamic law in Banda Aceh. The research method used is descriptive method with a qualitative approach. The formulation and implementation carried out by the Wilayatul Hisbah institution of Banda Aceh City has been carried out in accordance with the basic values of strategic management governance, quality and justice.